2021
DOI: 10.1037/xhp0000949
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic forms affect speech perception in a second language: Consonant and vowel length in L2 English.

Abstract: ItalianL1 speakers of EnglishL2 produce the same English sound as longer if spelled with two than with one letter, following Italian grapheme-phoneme conversion rules. Do Italian listeners perceive short and long sounds in English homophonic word pairs that are spelled with a single letter or a digraph (finish-Finnish; morning-mourning)? In Experiment 1, 50 ItalianL1-EnglishL2 bilinguals and 50 English controls performed a Consonant Perception Task and a Vowel Perception Task. They heard English homophonic wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Such results confirm and extend previous findings that orthography-induced consonant gemination in Italian L1 speakers of English L2 is persistent. Previous studies found that it is not eliminated by extensive exposure in a target-language environment (Bassetti et al, 2018;Bassetti et al, 2020;Bassetti et al, 2021), although the same exposure can reduce other non-native like timing aspects of L2 speech production that are not reinforced by orthography (Mairano et al, 2018). Furthermore, the metalinguistic awareness task results extend such findingsthat orthographic effects on L2 phonology are persistent-from speech production to metalinguistic awareness.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Such results confirm and extend previous findings that orthography-induced consonant gemination in Italian L1 speakers of English L2 is persistent. Previous studies found that it is not eliminated by extensive exposure in a target-language environment (Bassetti et al, 2018;Bassetti et al, 2020;Bassetti et al, 2021), although the same exposure can reduce other non-native like timing aspects of L2 speech production that are not reinforced by orthography (Mairano et al, 2018). Furthermore, the metalinguistic awareness task results extend such findingsthat orthographic effects on L2 phonology are persistent-from speech production to metalinguistic awareness.…”
Section: Discussionsupporting
confidence: 64%
“…We decided to implement an intervention addressing the GPCs of English consonant and vowel digraphs because exposure to English native speech by itself does not eliminate orthographic effects on L2 phonology and because explicit phonetic instruction can impact L2 speech production. Lengthy naturalistic exposure does not appear to reduce the effects of number of letters (single or digraphs) on second language phonology in Italian L1 speakers of English L2 (Bassetti et al, 2018;Bassetti et al, 2020;Bassetti et al, 2021). Researchers also found that sequential bilinguals with lengthy naturalistic exposure produced more native-like voice onset times than instructed learners, but did not produce fewer long consonants (Mairano et al, 2018), and argued that the effects of orthography on timing in L2 speech production may be more impervious to change than effects of L1 phonology that are not reinforced by orthographic representation.…”
Section: The Present Studymentioning
confidence: 93%
See 3 more Smart Citations